PENGARUH LOCUS OF CONTROL DAN PERILAKU DISFUNGSIONAL AUDIT TERHADAP KUALITAS AUDIT PADA KANTOR AKUNTAN PUBLIK DI SEMARANG (Studi Empiris Pada Kantor Akuntan Publik di Semarang) - Ida Perwati; Sutapa Sutapa (Jurnal Akuntansi Indonesia, 2016)
This study aims to look at the effect of variable locus of control, dysfunctional behavior premature sign off and dysfunctional behavior underreporting of time to audit quality in the public accounting firm in Semarang. The study population was the auditors who work in public accounting in Semarang. 2015. The sampling technique in thisstudy using convenience sampling.Jenis data used in this study are derived from primary data from respondents’ answers to the questionnaire that has been distributed on each - each KAP in Semarang. Data quality test results which consist of validity and reliability testing manunjukan that all variables can be said tobe valid and reliable so for the next item - the item on each - each concept is feasible variable is used as a measuring tool. Classical assumption that includemulticollinearity test, heteroscedasticity test, and Uju normality shows that the linear method used to qualify for a statistical test to the regression model. From the results of statistical tests showed that the locus of control with sig.0,147 and behavioral variables sig disfugioal premature sign off with the value sig.0,597, Showing that these two variables did not significantly affect audit quality, and underreporting of time with sig.-.058 , has a negative effecton audit quality.